2016
DOI: 10.1536/ihj.15-435
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Wiring Technique to Insert a Retrograde Guidewire Directly Into the Antegrade Guiding Catheter at the Ascending Aorta for Retrograde Percutaneous Recanalization of an Ostial Coronary Total Occlusion

Abstract: SummaryIn recent years, the use of a retrograde approach has become a common practice in the treatment of chronic total occlusion (CTO) of the coronary ostium and artery with an anomalous origin. Use of this approach has increased the chances of a successful percutaneous coronary intervention (PCI). However, the approach requires capturing the retrograde guidewire within the aorta, which can often pose a problem. Therefore, we developed a technique in which the retrograde guidewire is passed through the CTO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Web-based research shows there are publications about retrograde coronary interventions via the saphenous vein graft, but there is only 1 case report about successful retrograde recanalization of a chronic ostial occlusive lesion of the LMCA via a saphenous vein graft. 2-6 The drilled balloon technique was not used in these studies. We think that the drilled balloon technique facilitates this process.…”
Section: Discussionmentioning
confidence: 99%
“…Web-based research shows there are publications about retrograde coronary interventions via the saphenous vein graft, but there is only 1 case report about successful retrograde recanalization of a chronic ostial occlusive lesion of the LMCA via a saphenous vein graft. 2-6 The drilled balloon technique was not used in these studies. We think that the drilled balloon technique facilitates this process.…”
Section: Discussionmentioning
confidence: 99%
“…16) However, over the last several years, significant progress in technology, materials, techniques, and operator experience in PCI CTO improved procedural success to almost 90%, and more. [17][18][19][20][21][22] Regarding mortality, a report from the UK Central Cardiac Database showed that successful CTO intervention was associated with improved long-term survival.…”
Section: Discussionmentioning
confidence: 99%